Insurance Market in the EU Countries and Lithuania: Analysis and Perspectives - Lezgovko, Aleksandra; Lastauskas, Povilas (Ekonomika, 2008)
Insurance is a very dynamic area, and to design it is a complicated task. This confusion arises because of insurance goals and impact variety and inconsistence. Independent insurance intermediators play an important role in the insurance sector. Their functioning, by the way, is very dynamic, constantly falling down, and increasingly approaching the role of service provider for customers and assurers. The choice of services is growing, already now agents and brokers render qualified consultations on the questions of management and designing, coordinate the interests of insurer and assurer, deal with insurer’s matters, and suggest new insurance products. This forces the market to become more competitive, stable, reliable and dynamic. Not always there is success in coordinating interests of assurers, their intermediators and insurers. There arises more ambiguity while evaluating the influence of insurance on the economy of the country and the welfare of each inhabitant. Despite this discrepancy, the majority of people agree that the existence of insurance gives liveliness for the economy and encourages investments, gives a sense of safety and activates business. Insurance perspectives in the EU and Lithuania ere reviewed, features of the present day insurance which has formed during the last years or is still fanning are discussed in the article.The EU case:The structure of the current insurance market is determined by the dominating purchase and mergers during the last decade. There is a belief, that assurers will increasingly specialize. In such a way, there will be looked for the opportunities to occupy the market share of a specific insurance branch, to pursue valuable information to ensure a competitive advantage.Private sector will become increasingly responsible for rising pensions, because the ageing of society causes more and more problems to the national insurance. From the macroeconomics point of view, it will encourage permanent saving, may depress inflation because of a reduced current consumption.New assurers, intermediators and insurance products force to develop a new sales network, thus in the nearest future we will see the methods of combined sales, a wider usage of information technologies which enable to evaluate every individual risk and provide an advantage of convenience for the customer.The case of Lithuania:The Lithuanian insurance market has bigger opportunities of expansion, confirmed by low indexes of insurance development. Besides that, it is believed that the existing environment is very favourable for the growth - there occurs social insurance transition to the private sector, foreign capital enterprises bring good experience, raise claims of quality, there is an integration between insurance enterprises and banks.Life insurance will expand more in comparison with non-life insurance. The development levels of these insurance types and performed reforms, the rise of income disposed by individuals and thus better opportunities for the future testify to this.It is believed that the number of insurance enterprises may reduce because of international tendencies which force assurers to increase their market share, in such a way reducing risk management prices, also after confrontation with concrete troubles, regulation which is becoming more complex (for instance, Solvency II), and because of other reasons.